Cross Dataset Evaluation for IoT Network Intrusion Detection - (:unkn) unknown (My University, 2020)
With the advent of Internet of Things (IOT) technology, the need to ensure the security of an IOT network has become important. There are several intrusion detection systems (IDS) that are available for analyzing and predicting network anomalies and threats. However, it is challenging to evaluate them to realistically estimate their performance when deployed. A lot of research has been conducted where the training and testing is done using the same simulated dataset. However, realistically, a network on which an intrusion detection model is deployed will be very different from the network on which it was trained. The aim of this research is to perform a cross-dataset evaluation using different machine learning models for IDS. This helps ensure that a model that performs well when evaluated on one dataset will also perform well when deployed. Two publicly available simulation datasets., IOTID20 and Bot-IoT datasets created to capture IOT networks for different attacks such as DoS and Scanning were used for training and testing. Machine learning models applied to these datasets were evaluated within each dataset followed by cross -dataset evaluation. A significant difference was observed between the results obtained using the two datasets. Supervised machine learning models were built and evaluated for binary classification to classify between normal and anomaly attack instances as well as for multiclass classification to also categorize the type of attack on the IoT network.
Keywords: Cross dataset evaluation; Intrusion detection; IoT; Machine Learning; Network IDS